Effects of Heat Treatment Ageing on the Microstructure, Mechanical Properties and Wear Resistance of Duplex Stainless Steels. - Turhan, Huseyin (Carl Hanser Verlag, 2010)
Effects of Heat Treatment Ageing on the Microstructure, Mechanical Properties and Wear Resistance of Duplex Stainless Steels. The effects of heat treatments like quenching, aging and homogenization on the microstructure and mechanical properties of aduplex stainless steel have been examined. The test specimens, which have been prepared as to ASME 1883, had a low Mo content and respectively high C, Cr and Ni contents. They were heated up to 1060 degrees C and quenched in ice water with 3.5 % NaCl to obtain a duplex microstructure that consists of austenite and ferrite phases. After quenching, the samples were aged at 475, 650 and 850 C, respectively, for 80 h and cooled rapidly. Then all the samples were examined with X-ray diffraction and SEM in order to determine the intermetallic phases and carbides.In addition, the mechanical properties of all specimens have been determined.It was found that the mechanical properties of the specimens were quite different. DTA (differential thermal analysis) curves also showed that austenite phase completely transformed into the ferrite phase between 1100 degrees C and 1221 degrees C.